Exploring Academic Salaries in a Comparative Context - Pacheco, Ivan; Rumbley, Laura (International Higher Education, 2008)
In 2007, the Boston College Center for International Higher Education (CIHE) launched an exploratory project attempting to do just that collecting and comparing salary data (in World Bank PPP dollars) from 15 countries and one territory. We looked at target countries' relative positions on the Human Development Index (HDI) of the United Nations Development Program for comparative analysis. In terms of salary progressions over the course of a career, our data show that faculty in wealthier, more developed countries tend to enjoy greater potential for salary growth with some exceptions. Comparing faculty salaries to average per capitaincome estimates indicates that the academic profession pays well in many parts of the developing world. Given this simple reality, faculty salaries stand out as a subtle but important consideration in any national development conversation and in the race for international relevance.